أساليب التعامل مع مواقف الحياة الضاغطة لدى كبار السن المقيمين بدور العجزة في ظل زمن انتشار فيروس كورونا (Covid-19) في الجزائر - قاسمي، إيمان (جامعة العربي بن مهيدي - أم البواقي, 2021)
تهدف الدراسة الحالية إلى الكشف عن أساليب التعامل مع مواقف الحياة الضاغطة لدى كبار السن المقيمين بدار العجزة في ظل زمن انتشار فيروس كورونا المستجد (Covid-19) في الجزائر، بالإضافة إلى معرفة الفروق المتواجدة في التعامل مع تلك الضغوط باختلاف جنس كبار السن. ولتحقيق أهداف الدراسة تم تطبيق مقياس أساليب مواجهة الضغوط النفسية للمسنين على (40) مسن، كما اعتمدنا المنهج الوصفي التحليلي، وبعد معالجة النتائج إحصائيا بواسطة البرنامج الإحصائي (SPSS) توصلنا إلى أن أغلبية كبار السن المقيمين بدار العجزة لديهم مستوى التعامل مع مواقف الحياة الضاغطة مرتفع، كما أنه لا يوجد اختلاف في التعامل مع تلك الضغوط باختلاف جنس عينة دراستنا." The present study aims to discover methods of treating stressful situations in the elderly residing in the nursing home in the light of the epidemic of the Corona virus (Covid-19) in Algeria, in addition to knowing the differences in the treatment of these pressures according to the sex of the elderly. To achieve the objectives of the study, a measure of methods to deal with the psychological pressures of the elderly was applied to (40) elderly, and we also adopted the descriptive analytical approach, and after the results were statistically treated by the Statistical Program (SPSS), we found that the majority of seniors residing in the nursing home have a high level of treatment for stressful life situations and there is no difference in the management of these pressures according to the gender of our study sample."
Keywords: الضغوطات النفسية -- فيروس كورونا "كوفيد-19" -- مرحلة الشيخوخة -- المجتمع الجزائري